Effect of Salinity Differences for Growth Chlorella sp. on the Laboratory Scale - Ais Anantama Wibowo; Hariyadi Hariyadi; Riza Rahman Hakim (IJOTA (Indonesian Journal of Tropical Aquatic), 2023)
Chlorella sp. growth is dependent on environmental conditions. One of environmental condition affect the growth of Chlorella sp. is salinity. Salinity can affect the growth of Chlorella sp. because salinity affects the osmosis pressure on the cell wall of Chlorella sp. in the absorption of nutrients in the culture media. This study aims to determine the effect of different salinity on the growth of Chlorella sp. This study was conducted on laboratory scale using experimental methods. This research used Walne fertilizer on culture media were given Chlorella sp. as many as 100,000 cells / ml in every treatment. This study uses 4 treatments and 3 repetitions. The treatment in this study with salinity differences, namely salinity 15 ppt, 20 ppt, 25 ppt and 30 ppt. Chlorella sp. growth data every day obtained from the calculation of the sample Chlorella sp. use haemocytometer. The calculation data obtained is then analyzed using anava one factor data. The results showed that differences in salinity had no effect on the growth of Chlorella sp. The best salinity for the growth of Chlorella sp. is at 15 ppt salinity with the number of Chlorella sp cells. at peak growth as much as 340 × 104 cells / ml, followed by treatment B salinity 20 ppt as much as 339.33 × 104 cells / ml, then treatment D salinity 30 ppt as much as 270.58 × 104 cells / ml, and treatment C 25 salinity as much as 266.83 × 104 cells / ml. Salinity of 15 ppt, 20 ppt, 25 ppt, and 30 ppt can be used for cultivation Chlorella sp.